Practice of Institutional Auditing Within the Education Quality Management System - Liudmyla ILICH; Olena AKILINA; Alla PANCHENKO (Communications of International Proceedings, 2020)
Purpose: The objective of this article is to develop tools of intelligent education quality management, analyze the elements of institutional audit and its introduction into practice of school operation. Methodology: While doing research the following methods were used: method of expert evaluations, data analysis, method of experiments, sociological methods, observation, and survey. The paper analyses foreign experiences and Ukrainian practices concerning reforms introduction into educational and management processes of school operating. We consider institutional auditing as a conceptually new approach to external assessment of school operation in contrast to their certification which is of oversight nature and serves as a tool of school support. Recommendation on school operation improvement is also the result of institutional auditing. Its main stage includes school self-evaluation which is widely used while carrying out experimental work at schools. Based on the results of theoretical analysis and experimental research, it is supposed that scientific organization of education quality monitoring enables to make relevant management decisions and forecast educational and training situations for further academic year, intervene promptly and implement appropriate corrections to pedagogical process, plan specifically the work on relevant challenges with both teachers and pupils, create the conditions for comparison own assessment of pedagogical staff operation and independent external experts’ evaluation. Conclusions: Institutional auditing confirms that, first and foremost, its effectiveness depends on systematical school self-evaluation at different stages of its operating and researching aspects of its operation that encourage school education quality improvement. As the results of this study testify, experimental work at school promoted improvement of pupils’ performance improvement, their cognitive interests’ development, as well as provides progressing of pedagogical staff’s professional skills. The results of experimental work serve the example of schools preparation for institutional audit as an external assessment of education quality assurance. Implications: The results of experimental studies serve as an example of schools preparation for institutional audit to evaluate education quality assurance externally. The development and implementation of bilingual education model is the result of experimental studies (2008-2020). Due to the introduction of bilingualism the students gain opportunities to improve their language skills at the courses in Institute Grand Bleu (Cannes, France), Alliance Française (Strasbourg, France), to be involved into exchange programs between schools and College des Alberts (Argelès-sur-Mer, France) and Lyceum (Rethel, France) according mutual agreements, to participate in French-speaking and English-speaking sessions of European Youth Parliament which take place at schools etc.
Keywords: Institutional Audit; Educational Establishment; Quality; Monitoring.